Geneza i początki pisma neogotyckiego na terytorium niemieckojęzycznej Europy = The origin and the beginning of the Neo-Gothic writing on the territory of german speaking Europe - Miżdal, Agata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article 'The origin and the beginning of the Neo-Gothic writing on the territory of German speaking Europe' makes an attempt to trace the origin of the Neo-Gothic writing. Therefore, documents from Bozen - a place regarded as the birthplace of Neo-Gothic (paleographic repertory in the Faculty of History in the University of Warsaw's- A copy book of the Bozen City Council as of 1520) have been compared with the sources from a collection of documents concerning Żagań's duchy in rhe years 1472-1549 found in Dresden's archives.
Keywords: pismo neogotyckie - badanie